RENAL SAFETY OF PROTON PUMP INHIBITORS - A. I. Dyadyk; T. E. Kugler (Архивъ внутренней медицины)
Proton pump inhibitors are a widely used in clinical practice, and are taken by millions of patients around the world for a long time. While proton pump inhibitors are well-tolerated class of drugs, the number of publications has been raised about adverse renal effects, specially their association with acute tubulointerstitial nephritis. It is one of the leading causes of acute renal injury and have catastrophic long-term consequences called chronic kidney disease. In this review, we consider epidemiology, pathogenesis, diagnostic criteria (including biopsy and morphological pattern), clinical manifestations and treatment of proton pump inhibitors-induced acute tubulointerstitial nephritis. A subclinical course without classical manifestations of a cell-mediated hypersensitivity reaction (fever, skin rash, eosinophilia, arthralgia) is characteristic of acute tubulointerstitial nephritis. Increased serum creatinine, decreased glomerular filtration rate, electrolyte disorders, pathological changes in urine tests are not highly specific indicators, but allow to suspect the development of acute tubulointerstitial nephritis. The “gold” standard of diagnosis is the intravital morphological examination of the kidney tissue. Timely diagnosis and immediate discontinuation of the potentially causative drug is the mainstay of therapy and the first necessary step in the early management of suspected or biopsy-proven drug-induced acute tubulointerstitial nephritis. The usage of proton pump inhibitors should be performed only on strict indications with optimal duration of treatment and careful monitoring of kidney function. Multiple comorbidities (older age, heart failure, diabetes, cirrhosis, chronic kidney disease, hypovolemia) increase potential nephrotoxicity. Awareness of this iatrogenic complication will improve diagnosis of proton pump inhibitors-induced acute tubulointerstitial nephritis by multidisciplinary specialists and increase the possibility of successful treatment.